Penyusunan Modul Pelatihan Kecerdasan Sosial Emosional Untuk Menurunkan Kecenderungan Agresi Pada Remaja - Garvin Garvin; Fifi Juniarti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
One of a way to deal with the demographic bonus is to prepare the human resources well. Today's adolescents will be working and professional in a few years. Unfortunately, adolescents who behave aggressively, instead, involve themselves in dangerous actions that distance them from the qualities that are expected to face the demographic bonus. Previous research has shown that emotional and social intelligence can help adolescents to reduce aggression and behave in a more appropriate manner. This research is aimed to develop a social-emotional intelligence training module and validating the module. The module was compiled through a literature study and then validated by three experts, namely (1) an emotional intelligence coach and trainer, (2) the principal, and (3) the teacher. The three experts shared information that this module was appropriate for training social-emotional skills in adolescents. The researchers concluded that this module can be used as character training material for adolescents. Researchers suggest that this module should also be tested directly on adolescents.